Textile Manufacturing Processes 2019
DOI: 10.5772/intechopen.86439
|View full text |Cite
|
Sign up to set email alerts
|

Stab Resistant Analysis of Body Armour Design Features Manufactured via Fused Deposition Modelling Process

Abstract: Five designs of imbricate scale armour features for stab-resistant application were printed via fused deposition modelling process. Stab test on these designs against the HOSDB KR1-E1 stab-resistant body armour standard with impact energy of 24 Joules was conducted. The stab test was conducted on a number of samples measured thicknesses ranging from 4.0 to 10.0 mm by using Instron CEAST 9340 Drop Impact Tower to determine a minimum thickness that resulted in a knife penetration through the underside of sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Besides, the authors report that polycarbonate (PC) and tough PLA (TPLA) were found most suitable for stab resistance, necessitating structures of only 5 mm thickness. Similar results were reported by Maidin et al who used FDM printing of ABS and PC-ABS samples which were tested according to HOSDB KR1-E1 with an impact energy of 24 J, and fractured samples were found in many cases, where PC-ABS showed higher stab resistance than ABS, and an optimum thickness of 8.0 mm was defined [ 46 ].…”
Section: 3d Printed Polymer-based Body Armorsupporting
confidence: 79%
“…Besides, the authors report that polycarbonate (PC) and tough PLA (TPLA) were found most suitable for stab resistance, necessitating structures of only 5 mm thickness. Similar results were reported by Maidin et al who used FDM printing of ABS and PC-ABS samples which were tested according to HOSDB KR1-E1 with an impact energy of 24 J, and fractured samples were found in many cases, where PC-ABS showed higher stab resistance than ABS, and an optimum thickness of 8.0 mm was defined [ 46 ].…”
Section: 3d Printed Polymer-based Body Armorsupporting
confidence: 79%
“…Proposed solutions for stab protection include panels inspired by animal protection [3][4][5][6][7][8][9], either in the form of whole boards [10], profiled, or panels made of scale-like components [11][12][13], eggshells [14], or pads [15][16][17], their production being possible even by additive manufacturing [18][19][20]. Research has also been reported on vests with fluids that change their viscosity under impact, consuming a substantial part of the impact energy [14,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The dual-layered imbricated assembly arranged at a 14.3° assembly angle effectively reduces penetration depth (Johnson et al , 2017). However, most scales need to design additional link structures during assembly, and then tilt to form imbricated structures (Maidin et al , 2019). This increases the overall thickness of the material and the area of weak joints.…”
Section: Introductionmentioning
confidence: 99%